Antioxidant Activity of Unripe Sapodilla Fruit Extract (Manilkara zapota L.) through Nrf2 and SOD Expression in Type 1 Diabetic Mice: Antioxidant activity of Manilkara zapota extract in T1DM - Muhaimin Rifa'i; Fikriya Novita Sari; Rizky Senna Samoedra; Setyaki Kevin Pratama; Sri Rahayu; Aris Soewondo; Muhammad Halim Natsir (Journal of Tropical Life Science, 2023)
This research aims to analyze the effect of unripe sapodilla fruit extract on endogenous antioxidant expression in T1DM BALB/c mice and its free radical scavenging activity. Manilkara zapota extract (MzE) is an aqueous extract of unripe sapodilla fruit and was obtained by maceration and freeze-drying process. This study used 25 male BALB/c mice with 7-weeks-old of age. They were divided randomly into five groups (n=5) before treatment. A single high dose (145 mg/kg BW) of streptozotocin (STZ) was intraperitoneally injected to induce type 1 diabetes mellitus (T1DM). MzE was given orally once each day for 14 days. Liver cells were isolated and immunoassay with anti-superoxide dismutase (SOD) and anti-nuclear factor erythroid 2-related Factor 2 (Nrf2), and then the results were analyzed by flow cytometry. Diphenylpicrylhydrazyl (DPPH) assay was performed to analyze free radical scavenging. Data were analyzed statistically with one-way ANOVA (p<0.05). The result showed that the glucose levels in diabetic mice after MzE administration were significantly lower than in the DM group. MzE treatment increased the expression of Nrf2 and SOD in diabetic mice. MzE could scavenge DPPH with the IC50 value obtained at 48.35 μg/mL, while ascorbic acid as a control could scavenge DPPH with the IC50 value at 22.24 μg/mL. The increase in the scavenging activity is in line with the increase in extract concentration. In conclusion, this study revealed that MzE can be an endogenous antioxidant enhancer by improving the expression of Nrf-2, SOD and can inhibit free radicals as an exogenous antioxidant in T1DM.